UPAYA MENINGKATKAN PRESTASI BELAJAR PAI DAN BUDI PEKERTI DENGAN MENERAPKAN MODEL PEMBELAJARAN PAIKEM - MARLINA HIDAYANTI ANSANOOR (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
The success of the teaching and learning process in the classroom is largely determined by the learning strategy. However complete and clear the other components, without being implemented through the right strategy, these components will have no meaning in the process of achieving goals. Therefore, each teacher will be required to apply certain strategies or methods in the implementation of learning. The aims of this study are 1) Want to know the improvement of student achievement in X-9, 2015/2016 academic year after the implementation of the PAIKEM learning model, 2) Want to know the effect of PAIKEM learning model on learning achievement of Islamic Religious Education in X-9 grade students in 2015 academic year. /2016. This research is based on the following problems: 1) How is the improvement of Islamic Religious Education learning achievement with the implementation of the PAIKEM learning model in class X-9 students in the 2015/2016 academic year. 2) How is the effect of the PAIKEM learning model on the learning achievement of Islamic Religious Education in class X-9 students in the 2015/2016 academic year. This research is an action research with two cycles. Each round consists of four stages, namely: design, activities and observations, reflection and revision. The target of this research is the students of class X-9. The data obtained in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis, it was found that the learning achievement of class X-9 students in the 2015/2016 academic year experienced an increase in learning mastery in each cycle, namely para-cycle (69.23%), cycle I (80.77%), cycle II (92, 31%). The conclusion of this study is that the PAIKEM learning model can have a positive effect on student achievement in class X-9 in the 2015/2016 academic year, and this learning model can be used as an alternative method of learning Islamic Religious Education subjects. ABSTRAKKeberhasilan proses belajar mengajar di dalam kelas sangat ditentukan oleh strategi pembelajaran. Bagaimanapun lengkap dan jelasnya komponen lain, tanpa diimplementasikan melalui strategi yang tepat, maka komponen-komponen tersebut tidak akan memiliki makna dalamm proses pencapaian tujuan. Oleh karena itu setiap akan mengajar guru diharuskan untuk menerapkan strategi atau metode tertentu dalam pelaksanaan pembelajaran. Tujuan penelitian ini adalah 1) Ingin mengetahui peningkatan prestasi belajar siswa X-9, tahun pelajaran 2015/2016 setelah diterapkannya model pembelajaran PAIKEM, 2) Ingin mengetahui pengaruh model pembelajaran PAIKEM terhadap prestasi belajar Pendidikan Agama Islam pada siswa kelas X-9 tahun pelajaran 2015/2016. Penelitian ini berdasarkan permasalahan : 1) Bagaimanakah peningkatan prestasi belajar Pendidikan Agama Islam dengan diterapkannya model pembelajaran PAIKEM pada siswa kelas X-9 tahun pelajaran 2015/2016. 2) BAgaimanakah pebgaruh model pembelajaran PAIKEM terhadap prestasi belajar Pendidikan Agama Islam pada siswa kelas X-9 tahun pelajaran 2015/2016. Penelitian ini merupakan penelitian tindakan (action research) sebanyak dua siklus. Setiap putaran terdiri dari empat tahap yaitu : rancangan, kegiatan dan pengamatan, refleksi dan revisi. Sasaran penelitian ini adalah siswa kelas X-9. Data yang diperoleh berupa hasil tes formatif, lembar observasi kegiatan belajar mengajar. Dari hasil análisis didapatkan bahwa prestasi belajar siswa kelas X-9 tahun pelajaran 2015/2016 mengalami peningkatan ketuntasan belajar dalam setiap siklus, yaitu para-siklus (69,23%), siklus I (80,77%), siklus II (92,31%). Kesimpulan dari penelitian ini adalah model pembelajaran PAIKEM dapat berpengaruh positif terhadap prestasi belajar siswa kelas X-9 tahun pelajaran 2015/2016, serta model pembelajaran ini dapat digunkan sebagai salah satu alternatif metode pembelajaran mata pelajaran Pendidikan Agama Islam.